2007
DOI: 10.1016/j.ijnurstu.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The values and qualities of being a good helper: A qualitative study of adult foster home caregivers for persons with serious mental illness

Abstract: Background-Canadian foster homes for adults with serious mental illness are operated by nonprofessional caregivers, usually women, whose mandate is to support residents and reintegrate them into the community. While mental health professionals recognize that adult foster homes are an important service for this population, there is little understanding of how caregivers impact on the lives of their residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…, Nadeau & Meacham , Piat et al . , O'Mahony & Donnelly , ). Mental health practitioners must also encourage the creation, funding, and evaluation of programmes for newcomers to reduce isolation and facilitate the social inclusion.…”
Section: Partmentioning
confidence: 99%
“…, Nadeau & Meacham , Piat et al . , O'Mahony & Donnelly , ). Mental health practitioners must also encourage the creation, funding, and evaluation of programmes for newcomers to reduce isolation and facilitate the social inclusion.…”
Section: Partmentioning
confidence: 99%
“…Most people with SMI who participated in the Community Family programme had lived much of their adult life in contact with the social services system, and some had lived in an institutional context. A qualitative study of professional foster families showed that interactions with people with SMI were guided by clearly articulated values and personal qualities such as patience, experience, self-mastery and good judgement (Piat, Ricard, Sabetti, & Beauvais, 2007). The overall conclusion was that caring for people with SMI requires knowledge and experience.…”
Section: Discussionmentioning
confidence: 99%
“…Arriver à rencontrer ses mensualités sans devoir se priver de besoins de base, dont une saine alimentation, est une première condition de rétablissement. Viennent ensuite les commodités qu'offre l'hébergement, l'espace dont on y dispose, la beauté des lieux et le quartier environnant, ce que la recherche a également reconnu comme des facteurs de rétablissement (Harkness, Newman et Salkever, 2004 ;Walker et Seasons, 2002 La contribution des relations sociales au rétablissement des personnes atteintes de troubles mentaux graves est largement documentée dans la littérature (Boydell, 2006 ;Browne et Courtney, 2005 ;Dayson, 1992 ;Dayson, Lee-Jones, Chahal et Leff, 1998 ;Piat, Ricard, Sabetti et Beauvais, 2007 ;Wright et Kloos, 2007 (Brunt et Hansson, 2004 ;Leff et al, 2009). …”
Section: Discussion Et Implicationsunclassified